The Pill is Mightier Than the Sword - Malcolm Potts; Aafreen Mahmood; Alisha A. Graves (Kerman University of Medical Sciences, 2015)
One determinant of peace is the role of women in society. Some studies suggest that a young age structure, also known as a "youth bulge" can facilitate conflict. Population growth and age structure are factors amenable to change in a human rights context. We propose that policies which favor voluntary family planning and the education of women can ameliorate the global burden of disease associated with conflict and terrorism.